Analisis Keamanan Website E-learning ILMU2 Menggunakan Metode Open Web Application Security Project ZAP (OWASP ZAP) - Shalsabila Titanie Harianto; Zahrah Aliyah Rachman; Aliyyah Nabiilah Farahdita; Fahryan Putra Ramadi; Agung Brastama; Siti Mukaromah (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The development of e-learning platforms has transformed the landscape of education by providing flexible and accessible learning methods. However, security threats targeting web-based applications pose significant risks to the confidentiality, integrity, and availability of academic data. This research aims to analyze the security vulnerabilities of the ILMU2 e-learning website at UPN “Veteran” Jawa Timur using the Web Application Security Project Zed Attack Proxy (OWASP ZAP) methodology. The study applies a black-box testing approach to simulate attacks and identify potential weaknesses in the website's security mechanisms. Expected findings include the identification of vulnerabilities such as cross-site scripting (XSS), SQL injection, and security misconfigurations. The results are intended to provide insights for improving the security posture of the ILMU2 platform and contribute to the broader discourse on securing educational technology in higher education institutions.